2006
DOI: 10.1086/507281
|View full text |Cite
|
Sign up to set email alerts
|

First Year of Mandatory Reporting of Healthcare-Associated Infections, Pennsylvania An Infection Control—Chart Abstractor Collaboration

Abstract: With ongoing training by Infection Control, Atlas successfully demonstrated a role in retrospective HAI surveillance. However, despite a major effort to comply with mandates, time lags and other design limitations rendered the data of low utility for Infection Control. States that are planning HAI-reporting programs should standardize an efficient surveillance methodology that yields data capable of guiding interventions to prevent HAI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 5 publications
(2 reference statements)
0
13
0
Order By: Relevance
“…[15] However, automated surveillance may be a poor proxy for conventional HAI surveillance (particularly when utilising the 10th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10) coding), with both false positives and missed HAI events reported. [16][17][18] Computerised HAI identification algorithms that use multiple sources of information (e.g. laboratory data, ICD-10 coding and inpatient prescriptions) can achieve better sensitivity and positive predictive values (PPVs).…”
Section: Researchmentioning
confidence: 99%
“…[15] However, automated surveillance may be a poor proxy for conventional HAI surveillance (particularly when utilising the 10th revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10) coding), with both false positives and missed HAI events reported. [16][17][18] Computerised HAI identification algorithms that use multiple sources of information (e.g. laboratory data, ICD-10 coding and inpatient prescriptions) can achieve better sensitivity and positive predictive values (PPVs).…”
Section: Researchmentioning
confidence: 99%
“…Some authors have concluded that billing and claims data cannot be reliably used for SSI surveillance. 4,9,10 We found that 94.3% of patients identified as having an SSI by our rigorous claims algorithm also received clinically expected treatment for infection; a more conservative PPV estimate excluding culture was still very high, at 89.5%. While we could not confirm the SSIs with medical chart review, our results suggest that the claims algorithm we used to identify SSIs has very good PPV.…”
Section: Discussionmentioning
confidence: 81%
“…59 Studies completed before the 2008 CMS rule generally concluded that claims data overestimated the incidence of HAI compared with traditional IC methods by approximately 5 to 1. 5,6 A study by Stevenson et al 5 estimated a 15% PPV for CLABSI identified with a set of multiple ICD-9 codes compared with traditional IC.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors who have studied this topic emphasize that billing data are inaccurate when compared with traditional surveillance methods. 59 At present, there is no measure of central line–related bloodstream infection that perfectly reflects clinical truth. Traditional IC methods have been previously criticized for elements of subjectivity and are considered a proxy measure for the true, unknown incidence.…”
mentioning
confidence: 99%